Adaptation and validation of the Maslach Burnout Inventory in Argentinian mental health professionals - Gilla, María Antonella (2019)
Objective: the aim of this instrumental study was to adapt the Spanish version of the Maslach Burnout Inventory - Human Services Survey (MBI-HSS) in a sample (n = 544) of Argentinian psychologists and psychiatrists aged 23 to 71. Method: a confirmatory factor analysis (CFA) was conducted to evaluate the internal structure of the instrument using the robust maximum likelihood estimation. Additionally, the internal consistency was calculated using the composite reliability (CR) coefficient. Results: the original structure provided an acceptable ût to the data (CFI = .87, TLI = .86, RMSEA = .06, SRMR = .07). However, the three-factor model had a closer fit to the data after excluding item 12 from the analysis (CFI = .91, TLI = .90, RMSEA = .05, SRMR = .06). The internal consistency yielded very good values (CR > .70). Conclusion: it is concluded that the MBIHSS is a reliable and valid scale to measure burnout in Argentinian psychologists and psychiatrists. The results and their possible implications for future investigations are discussed in this paper.